Estimation of interplanetary electric field conditions for historical geomagnetic storms - Kumar, Sandeep; Veenadhari, B.; Tulasiram, S.; Selvakumaran, R.; Mukherjee, S.; Singh, Rajesh; Kadam, B.D. (JGR, 120, p. 7307–7317, doi: 10.1002/2015JA021661, 2015)
Ground magnetic measurements provide a unique database in understanding space weather. The continuous geomagnetic records from Colaba-Alibag observatories in India contain historically longest and continuous observations from 1847 to present date. Some of the super intense geomagnetic storms that occurred prior to 1900 have been revisited and investigated in order to understand the probable interplanetary conditions associated with intense storms. Following Burton et al. (1975), an empirical relationship is derived for estimation of interplanetary electric field (IEFy) from the variations of Dst index and ΔH at Colaba-Alibag observatories. The estimated IEFy values using Dst and ΔHABG variations agree well with the observed IEFy, calculated using Advanced Composition Explorer (ACE) satellite observations for intense geomagnetic storms in solar cycle 23. This study will provide the uniqueness of each event and provide important insights into possible interplanetary conditions for intense geomagnetic storms and probable frequency of their occurrence
Keywords: Geomagnetic storms; Advanced composition explorer satellite; Solar cycle 23; ACE satellite; Ring current in storms